CaMK II Inhibition Attenuates ROS Dependent Necroptosis in Acinar Cells and Protects against Acute Pancreatitis in Mice - Qingtian Zhu (Hindawi Limited, 2021)
As a calcium-regulated protein, CaMK II is closely related to cell death, and it participates in the development of pathological processes such as reperfusion injury, myocardial infarction, and oligodendrocyte death. The function of CaMK II activation in acute pancreatitis (AP) remains unclear. In our study, we confirmed that the expression of p-CaMK II was increased significantly and consistently in injured pancreatic tissues after caerulein-induced AP. Then, we found that KN93, an inhibitor of CaMK II, could mitigate the histopathological manifestations in pancreatic tissues, reduce serum levels of enzymology, and decrease oxidative stress products. Accordingly, we elucidated the effect of KN93 in vitro and found that KN93 had a protective effect on the pancreatic acinar cell necroptosis pathway by inhibiting the production of ROS and decreasing the expression of RIP3 and p-MLKL. In addition, we identified the protective effect of KN93 on AP through another mouse model induced by pancreatic duct ligation (PDL). Together, these data demonstrated that CaMK II participates in the development of AP and that inhibiting CaMK II activation could protect against AP by reducing acinar cell necroptosis, which may provide a new idea target for the prevention and treatment of AP in the clinic.